The Meaning of Symbolic Aesthetic of Basic Shapes in Sundanese Culture - J. Jamaludin; Anwar Subkiman; Edwin Widia (Mudra Jurnal Seni Budaya, 2024)
This paper aims to examine the symbolic aesthetic concepts that exist in Sundanese society and culture in West Java, Indonesia. The symbolic meaning that exists or is applied to forms that are known in art and design. With the method of interpretation and using Sundanese as a source of research, several expressions and proverbs are found that use the basic shapes, namely squares, triangles and circles. The results of this study indicate that there are symbolic meanings of the three basic forms which indicate that in Sundanese culture there is awareness of the existence of these basic forms and give them symbolic meanings. These basic forms are generally sourced from objects found in nature. The meaning of this basic form refers to a certain function that is applied according to the character of the basic form in its implementation. This symbolic meaning generally refers to efforts to create cultural values towards perfection. The meaning of this basic shape can be used for the meaning of the basic shape used in designs with a local cultural approach, especially in areas where the culture grows and develops.